Analisis Pemanfaatan Dana Corporate Social Responsibility Bagi Penerima Beasiswa Bank Nagari - Gigih Apriatma; Charoline Cheisviyanny; Salma Taqwa (Universitas Negeri Padang, 2019)
The purposes of this research are to analyze the benefits of recipients of Scholarship CSR Funds by Bank Nagari,the feedback for Bank Nagari and the provision of target benefits of CSR Funds by Bank Nagari. The subject of this research was students who received Bank Nagari scholarship. This research was a qualitative research. The type of data used in this research were primary and secondary data. Primary data was obtained from the results of in-depth interviews with students and secondary data was obtained from Bank Nagari's Annual report 2016. Data collection techniques were carried out by observation, interviews, and documentation. The results of this research indicated that the scholarship from Bank Nagari has benefits for recipients, while for feedback was directly not received by Bank Nagari, as well as for the overall awarded of scholarships was considered appropriate but there was different ways of register procedures.